Mendirikan Organisasi Remaja Musala sebagai Upaya Pemberdayaan Masyarakat - Nenie Sofiyawati (Jurusan Pendidikan Masyarakat Fakultas Keguruan Ilmu Pendidikan Universitas Siliwangi, 2023)
Adolescents who understand their potential have the ability to choose activities that can develop their talents and interests. Choosing the wrong environment has the effect of a crisis of morality and criminality. Musala Youth as a religious social organization can be used as an alternative in empowering adolescents to be more productive and conditioned in a positive environment. A Musala in Sidoarjo only functions as prayer. Musala still does not have activities that can empower teenagers even though some teenagers are affected by drug cases. This study uses a qualitative field approach through interview methods, participatory observation, and dialogical participation. Based on community service activities carried out at Musala Baiturrahim Taman Sidoarjo, stages can be formulated in establishing the Musala Youth organization, namely the work planning stage and work implementation. The work planning stage is the implementation of organizational and management theory while the work implementation stage is the implementation of management and leadership theory. The existence of musala youth organizations helps adolescents in training in organizational life, managing resources, and building social leadership.